Penelusuran Informasi Lulusan Program Studi Pendidikan Bahasa Indonesia Fakultas Bahasa dan Seni - Tusya'diah, Delima; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractShearch for information on graduates of Indonesian Language Study Programs a the Faculty of Language and Art. Paper. Library and Archives Information Study Program, Indonesia dan Regional Language and Literature Departement, Language and Art Faculty, Padang State University. In this paper we discuss the search for graduates of the UNP Language and Arts Faculty of Indonesia Language Study Program. The purpose of this study was to determine the profile of Indonesia Education Study Program graduates and to know the competency and employment of these graduation.Â The research method approach used is a qualitatif method. Data was collected using questionnaires. The location of this study was carried out on the application or distributing questionnaires through social media. The object of the search was the Inodesian Language Education alumni who responded to 47 alumni. The data collection technique was by sharing questionnaires through WhatsApp media. Analyze the data used by using the google form application.Â First based on the results of the study, concluded the following matters. Graduates of the Indonesian Language Study program every year do not settle or go up and down, many respondents are among women with the dominant year of entry in 2014, the lenght of the waiting period for employment before graduation 1-3 months while their first job is < 3 months. The two Indonesian Language Education alumni are mostly looking for work through the internet, the level, and they work in the education sector, both private and obtain the first salary of RP. 1.000.000 and the first salary of Rp. 1.000.000- IDR 2.000.000.Keyword: search; education; alumniÂ